2011
DOI: 10.1063/1.3600896
|View full text |Cite
|
Sign up to set email alerts
|

First results from the modular multi-channel dispersion interferometer at the TEXTOR tokamak

Abstract: Articles you may be interested in CO2 laser-based dispersion interferometer utilizing orientation-patterned gallium arsenide for plasma density measurements Rev. Sci. Instrum. 84, 093502 (2013);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…One example development for the application on W7-X is an interferometer to measure the line integrated density. The test measurements on the TEXTOR tokamak are described in Dreier et al 2011. The operational requirements of an interferometer combine very different time scales.…”
Section: Steady State Diagnosticsmentioning
confidence: 99%
“…One example development for the application on W7-X is an interferometer to measure the line integrated density. The test measurements on the TEXTOR tokamak are described in Dreier et al 2011. The operational requirements of an interferometer combine very different time scales.…”
Section: Steady State Diagnosticsmentioning
confidence: 99%
“…Hence, interpretation of the measured data is straightforward. Because good temporal and density resolution have already been confirmed with CO 2 lasers (wavelength 10.6 µm) [6][7][8][9], the DI is the most promising candidate. …”
Section: Alternative Density Measurement Methodsmentioning
confidence: 99%
“…Figure 2 shows a schematic view of the phasemodulated DI [6][7][8][9]. A mixed beam consisting of the fundamental and second harmonic components, which is generated with a nonlinear component, is used as a probe beam.…”
Section: Wavelength Selection For Demorelevant Helical Plasmasmentioning
confidence: 99%
“…Good progress had already been made with the development of this system 7 for W7-X when first impressive measurements on TEXTOR with a dispersion interferometer developed by the Budker Institute in Novosibirsk, Russia, demonstrated that this type of interferometer did not even during disruptions suffer from fringe jumps. 31 The beauty of this system is that in the measured signal any effects from retro-reflector vibrations or thermally induced changes in the laser path length cancel out entirely. This is achieved by creating an additional frequency doubled laser beam from a single, frequency stabilized crystal.…”
Section: Individual Diagnostic Specific Issuesmentioning
confidence: 99%